PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN - PAISAL . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
The purpose of this research is to know the influence of services quality to consumer’s satisfaction and also to know which variable that most dominant influence to the consumer’s satisfaction at Hotel Sentosa Palembang.  The data were collected by using interview and questionnaires.  The sample are 60 respondences who are staying at Hotel Sentosa.  The data were analyzed by using regression analysis follow by SPSS (Statistic Problem Solution Service) Version 11.5 software for windows.  The result shows that the services quality, they are Tangible, Reliability, Responsiveness, Assurance, and Empathy affect to consumers satisfaction are 33,5% while the remaining influenced by other factors outside the study, one of which is an easily accessible location factor.  Based on the t test (partial test), shows that there are three variables that influence of customers satisfaction partialy, they are responsiveness, assurance and empathy variable.  However, the most dominant variable is responsiveness variable.